A Reestruturação produtiva e o processo de trabalho em Catalão (Goiás): uma abordagem sobre o modo de vida da classe trabalhadora - PEREIRA, Leonardo Cesar (2012)
This study seeks to understand how the process of industrialization in Catalão (Goiás), represented by the installation of automakers, affects the way of life and the daily lives of workers at Mitsubishi Motors Corporation. The choice of our study subject is based on the perceptions of profound changes that the work process has brought about in the urban sociability, as a result of restructuring of productive capital, from 1970s. Making necessary to analyze the meanings of these changes to this region. This prerogative is grounded in theoretical knowledge produced by the historical-dialectical materialism and by documentary evidences about incentives and strategies for the implantation of industrial capital in the city of Catalão. From the perspective outlined above, we intend to develop the analysis about the labor as fundamental activity in mediating the metabolism of man with nature and its historical development, through the organization of work process and the impact of this process in the workers' way of life. The empirical analysis is substantiated by the study of the capitalist expansion process in the Catalão region, and by the consequent urbanization expansion and intensified industrialization in the recent years. From this context, we can understand the dynamics of the automotive sector in the city, especially the working and production processes at Mitsubishi. The impact on the way of life of workers is understood from the production and from urban life, as spaces for institutions of sociability. We conclude by pointing out classes' contradictions between the urban and industrial development and the way of life of Catalão's working class.